2006
DOI: 10.1109/tepm.2006.881764
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Numerical Investigation Into Multilayer Probe Card Layout Design

Abstract: This paper conducts experimental and numerical investigations into the microforce probing technique used to test the functionality of IC devices. The study commences by considering the case of a single tungsten needle probe and examines the relationship between the contact force and the scrub mark size on aluminum pads at various levels of overdrive and shooting angle. Subsequently, a three-dimensional computational model is developed to facilitate the design of an optimum multilayer needle card layout. The si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The nodes and elements of the meshed model were then input to ABAQUS for analysis purposes. In performing the simulations, the Young's modulus and Poisson's ratio of the needle were specified as 290.85 GPa and 0.28, respectively [2]. Furthermore, the pad was assumed to be a rigid body [8].…”
Section: Validation Of Optimization Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The nodes and elements of the meshed model were then input to ABAQUS for analysis purposes. In performing the simulations, the Young's modulus and Poisson's ratio of the needle were specified as 290.85 GPa and 0.28, respectively [2]. Furthermore, the pad was assumed to be a rigid body [8].…”
Section: Validation Of Optimization Resultsmentioning
confidence: 99%
“…In most practical applications, the contact force should not exceed 2.5 gf/mil and the scrub mark should terminate at a point no closer than 5-8 μm from the pad boundary [1]. The literature contains many numerical and experimental investigations into the relationship between the contact force and the scrub mark length in the probe testing of aluminum pads using a single tungsten needle [2]- [5]. In general, the results show that the contact force and the scrub mark length both increase with an increasing overdrive level.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical response of the aluminum pad is described by a linearly elastic-perfectly plastic constitutive model. The stressstrain relationship of the tungsten needle was obtained by tensile testing [12]. Table 2 briefly summarizes key characteristics of the mechanical behaviors of the components.…”
Section: Finite Element Modeling and Validationmentioning
confidence: 99%
“…Tan [11] used cantilever and membrane probe card to evaluate the reliability of the probe-before-bump process. While many studies have been done on before bump probing and AI pad probing with cantilever probe card [7][8], but few studies have reported on solder after bump probing research topic.…”
Section: Introductionmentioning
confidence: 99%